In For A Penny The Unauthorised Biography of Jeffrey Archer - Mantle, Jonathan (London, United Kingdom : Hamish Hamilton Ltd, 1988)
This biography of Jeffrey Archer examines the past and present, public and private faces of the bestselling author, ex-Deputy Chairman of the Conservative Party and self-made millionaire. It also considers the role of the one constant in his life, his wife, Mary.
List of illustrations -- In for a penny -- Keen and able -- Charity begins at home -- The class of '69 -- The crash of '74 -- The commercial traveller -- The prodigal son -- A matter of judgement -- After a decent interval.
Includes index.
Keywords: BIOGRAPHIES